Not all Christian nationalists are White (and not all White Christians are Christian nationalists): exploring the predictors of Christian nationalism - Everton, Sean F. (Frontiers in Social Psychology, 2024)
In recent years, the literature on Christian nationalism has grown exponentially. Studies have found that individuals who score high on a widely used Christian nationalism scale are likelier to advocate for traditional gender roles, endorse anti-immigrant policies, support policies limiting voting rights, oppose gun control and interracial marriage, express anti-vaccine attitudes, hold anti-globalist sentiments, and vote for Donald Trump. The literature on Christian nationalism is not without its critics, however. Some, for example, have questioned whether the scale used by many studies adequately identifies Christian nationalists and suggested alternative methods for doing so. Much of the literature also implicitly or explicitly equates Christian nationalism with white Christian nationalism, ignoring the fact that 25 to 30 percent of respondents who express Christian nationalist sentiments identify as Black, Hispanic, Asian, or another race or ethnicity. Finally, most of it has focused on the consequences of Christian nationalism. Very little has explored the predictors of Christian nationalism. The latter is the focus of this paper. Drawing on multivariate logistic regression, it examines potential factors driving Christian nationalist attitudes. It finds that age, whether someone identifies as a conservative or a Republican, biblical literalism, and frequent worship attendance are positively associated with Christian nationalism, while being affiliated with religious traditions other than evangelicalism (or having no affiliation at all) is negatively associated with it. Notably, race and ethnicity have no effect, suggesting that other factors may be at work. As such, the paper briefly considers four potential factors not readily captured by statistical analyses of cross-sectional data. It concludes by noting that if Christian nationalism is potentially undemocratic and dangerous, then concerned individuals need to focus as much time and energy on its predictors as its consequences.